Pengaruh Hasil Akreditasi Hak Pasien Dan Keterlibatan Keluaraga (HPK1) Terhadap Kualitas Pelayanan di RSUD Al Ihsan Provinsi Jawa Barat - Eri, Eri Wahyuni; Riyan Hadithya (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
This study aims to determine the magnitude of the influence of HPK1 accreditation results on the quality of services at Al Ihsan Hospital, West Java Province. The method used is a quantitative research method with the number of samples in this study is 125 respondents. The data collection techniques used were observation, interviews and distributing questionnaires. The data analysis method used is simple linear regression, linear regression coefficient and multiple correlation coefficient to explain the relationship and influence between independent and dependent variables. The results showed that the effect of HPK1 accreditation results on service quality had a result of 3% which was an influence between variables based on data processing results. This shows that the effect of HPK1 accreditation results on service quality at Al Ihsan Hospital, West Java Province, is very weak.